DEVELOPMENT OF VALUE AND SENSE CONSCIOUSNESS OF JUNIOR SCHOOLCHILDREN IN MATHEMATICS LESSONS (Pedagogy of Higher and Secondary Education, 2010)
In the articles demonstration experimental material of pedagogical model of the personality oriented lesson opens up on development of valuable-semantic consciousness ofpupils ofprimary classes on the lessons of mathematics.
Keywords: subject; interpsychical action of pupils on the lesson; developmenl of personality; having a special purpose orientation of action